2014
DOI: 10.1371/journal.pone.0112019
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Serum MicroRNA Signatures for Diagnosis of Mild Traumatic Brain Injury in a Closed Head Injury Model

Abstract: Wars in Iraq and Afghanistan have highlighted the problems of diagnosis and treatment of mild traumatic brain injury (mTBI). MTBI is a heterogeneous injury that may lead to the development of neurological and behavioral disorders. In the absence of specific diagnostic markers, mTBI is often unnoticed or misdiagnosed. In this study, mice were induced with increasing levels of mTBI and microRNA (miRNA) changes in the serum were determined. MTBI was induced by varying weight and fall height of the impactor rod re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 96 publications
5
45
0
Order By: Relevance
“…Of these, miR-99b-5p has been shown to be increased in circulation in mice 3 h after induction of mild traumatic brain injury (Sharma et al, 2014). However, in another study assessing serum microRNAs following a very different type and intensity of stress (3 days of immobilization and tail shock), a set of microRNAs distinct from those identified here were differentially expressed two weeks after stress .…”
Section: Discussionmentioning
confidence: 54%
“…Of these, miR-99b-5p has been shown to be increased in circulation in mice 3 h after induction of mild traumatic brain injury (Sharma et al, 2014). However, in another study assessing serum microRNAs following a very different type and intensity of stress (3 days of immobilization and tail shock), a set of microRNAs distinct from those identified here were differentially expressed two weeks after stress .…”
Section: Discussionmentioning
confidence: 54%
“…Plasma levels of miR-16 and miR-92a were shown to be elevated in humans following mild or severe TBI compared to controls (Redell et al, 2010). In mice, serum miRNA profiles were shown to be altered as early as 3h following a mild closed head injury compared to controls regardless of the severity of mild injury (Sharma et al, 2014). In adult rats, levels of let-7i were shown to be increased in both serum and CSF as early as 3h following blast TBI (Balakathiresan et al, 2012).…”
Section: Micrornas As Tbi and Sci Biomarkersmentioning
confidence: 99%
“…Sharma et al (2014) used a weight drop model and reported increasing mNSS-R scores with increased weight and height when mice were evaluated 1 day postinjury. Interestingly, in the same study, these investigators were unable to find an injury effect using a previous version of the NSS.…”
Section: Anticipated Resultsmentioning
confidence: 99%